An Exploration of School Counselor Small Group Work Experiences Leading Diversity Dinner Dialogues. Issue 2 (3rd April 2022) - Merlin-Knoblich, Clare; Mingo, Taryne M.; Saunders, Rachel
ABSTRACT: Given persistent evidence of discrimination toward students of color in K-12 schools, group dialogue about multiculturalism can help individuals understand and advocate for equity and inclusion. In this article, we introduce a new model for a multicultural dialogue intervention: Diversity Dinner Dialogues (DDDs). DDDs are a small group intervention that school counselors can implement to engage students and faculty/staff in dialogues about diversity. We also provide findings from a qualitative case study exploring the experiences of school counselors leading group work in DDDs. Five themes emerged suggesting that DDDs are valuable interventions and school counselors are well-positioned to lead them.